BMP signaling suppresses Gemc1 expression and ependymal differentiation of mouse telencephalic progenitors - Hanae Omiya; Shima Yamaguchi; Tomoyuki Watanabe; Takaaki Kuniya; Yujin Harada; Daichi Kawaguchi; Yukiko Gotoh (Scientific Reports, 2021)
Abstract The lateral ventricles of the adult mammalian brain are lined by a single layer of multiciliated ependymal cells, which generate a flow of cerebrospinal fluid through directional beating of their cilia as well as regulate neurogenesis through interaction with adult neural stem cells. Ependymal cells are derived from a subset of embryonic neural stem-progenitor cells (NPCs, also known as radial glial cells) that becomes postmitotic during the late embryonic stage of development. Members of the Geminin family of transcriptional regulators including GemC1 and Mcidas play key roles in the differentiation of ependymal cells, but it remains largely unclear what extracellular signals regulate these factors and ependymal differentiation during embryonic and early-postnatal development. We now show that the levels of Smad1/5/8 phosphorylation and Id1/4 protein expression—both of which are downstream events of bone morphogenetic protein (BMP) signaling—decline in cells of the ventricular-subventricular zone in the mouse lateral ganglionic eminence in association with ependymal differentiation. Exposure of postnatal NPC cultures to BMP ligands or to a BMP receptor inhibitor suppressed and promoted the emergence of multiciliated ependymal cells, respectively. Moreover, treatment of embryonic NPC cultures with BMP ligands reduced the expression level of the ependymal marker Foxj1 and suppressed the emergence of ependymal-like cells. Finally, BMP ligands reduced the expression levels of Gemc1 and Mcidas in postnatal NPC cultures, whereas the BMP receptor inhibitor increased them. Our results thus implicate BMP signaling in suppression of ependymal differentiation from NPCs through regulation of Gemc1 and Mcidas expression during embryonic and early-postnatal stages of mouse telencephalic development.